A tunable thermal switching device based on Joule heating-induced metalinsulator transition in VO2 thin films via an external electric field - Sukittaya Jessadaluk; Narathon Khemasiri; Prapakorn Rattanawarinchai; Sakon Rahong; Adirek Rangkasikorn; Navaphun Kayunkid; Supamas Wirunchit; Annop Klamchuen; Jiti Nukeaw (My University, 2019)
A solid state thermal switching device can regulate carrier transport by triggering of its critical transition temperature (Tc) by applied external thermal energy. Continuous control of the Tc of the thermal switch by the metal–insulator transition (MIT) phenomenon makes such devices widely usable. In this research, tunable thermal switching devices were fabricated, and characterization of the MIT in VO2 thin film phase transition material was studied as a function of temperature and the external applied electric field. We observed reversible abrupt changes of the electrical resistivity by approximately three orders of magnitude at Tc = 62.3 °C for VO2 thin film on a SiO2/Si substrate. The MIT induced by the external electric field successfully controlled the Tc of the thermal switch between 60 °C and 47 °C (as a linear relationship). We found that the Joule heating effect, rather than electric field breakdown, was a dominant mechanism due to the configuration of the device.
Keywords: Metalinsulator transition; Transition Metal Oxide Nanomaterials